CONTRASTING GRAIN SIZE AND COMPONENTRY IN COMPLEX PROXIMAL DEPOSITS OF THE 1886 TARAWERA BASALTIC PLINIAN ERUPTION - Carey R.J.; Houghton B.F.; Sable J.E.; Wilson C.J.N. (My University, 2007)
The 1886 Plinian eruption of Tarawera, New Zealand, is a unique basaltic fissure-fed eruption with exceptionally well preserved fall deposits to within 200 meters of the source vents. These proximal deposits form a series of spatter/cinder half-cones along the northeastern 8-km-long segment of the 1886 fissure. Here we examine these deposits using grain size and clast componentry techniques. We contrast the products of the phreatomagmatic (phases I and III) and Plinian (Phase II) stages of the eruption and examine deposit variability as a function of contrasting eruptive intensity within the climactic phase (II) of the eruption. The opening phreatomagmatic phase I of the eruption involved gas-rich magma interacting with water and fragmenting at least 300 meters below the surface. The deposits of the climactic phase that followed have relatively uniform grain size but marked contrasts in the relative abundance of juvenile and wall rock (lithic) clasts. Deposits linked to vents associated with the high Plinian plume are more uniform than those characterized by a weaker cone-forming eruption style. During the third, and closing, phase of the eruption, magma withdrawal accompanied the onset of decoupling of the exsolved gas phase, leading to fragmentation at increasingly greater depths and significant wall rock collapse into the erupting vents. Variability in eruptive style during phase II along the fissure appears to be a function of shallow seated controls, in particular the variable extent of incorporation of lithic wall rock into the erupting jet, as a consequence of vent wall collapse. Widely dispersed beds centralized around Plinian sources along the fissure have very low lithic content; cone-forming beds at other craters that contain very high lithic contents. This incorporation led to a significant reduction of the velocity and stability of the jet at these latter steep-walled craters, and induced episodicity in the form of vent-clearing explosions. The result is a large reduction of the physical and thermal ability of these vents to contribute to a stable high eruptive plume. Instead large volumes of ejecta were sedimented prematurely from shallow heights at rates an order of magnitude greater than for historical Strombolian, Hawaiian and subPlinian eruptions. This study illustrates that sustained powerful Plinian eruptions can be accompanied by heterogeneities and instabilities of the eruptive jet. At Tarawera, the record of complex proximal transport and deposition processes in the eruptive jet cannot be inferred from the eruption products at distances greater than 400 m from the eruptive fissure. We suggest that study of ultraproximal deposits, as seen at Mt Tarawera, provides the only opportunity to document the complex, dynamic behavior of the jet region of Plinian eruptions.
Keywords: PLINIAN ERUPTION; TARAWERA 1886; BASALTIC PLINIAN; FALL DEPOSIT